BRIGHT SOLITONS IN OPTICAL MEDIA WITH HIGH ORDER EFFECTS - Aliqulov, Muysin; Suyunov, Laziz (Innovatsion texnologiyalar, 2023)
In this article bright soliton solutions of the generalized nonlinear Schrödinger equation are found with the help of an effective potential, which is found too. The equation accounts second and fourth order dispersion and also third and fifth order nonlinearity of the media. For the obtained solutions their existence and stability regions are determined. The stability regions are verified and confirmed by solving the equation numerically.